APLIKASI TEKNOLOGI PANGAN DALAM PENGOLAHAN POTENSI LOKAL UMBI-UMBIAN DI DESA TAMANREJO KECAMATAN LIMBANGAN - Mudzanatun Mudzanatun; Khusnul Fajriyah; Iffah Muflihati (LP2M Universitas Hasanuddin, 2019)
Abstract. Processing of tubers as an abundant food ingredient in Tamanrejo Village which has not maximally processed brings problems that has resulted in a lack of partner income. Some of the factors that contributed to this problem included limited marketing areas, lack of product quality, and lack of entrepreneurial skills. The solution is given to answer partner problems in the form of application of food technology in the processing of tubers, business management, and marketing economics. The program of service activities is carried out in four stages, namely a) Identifying the problem; b) Program socialization; c) Extension and Training Program; and d) Monitoring and Evaluation. Activities carried out with farmer groups of women kelompok wanita tani/(KWT)